1996
DOI: 10.1080/0958517960070209
|View full text |Cite
|
Sign up to set email alerts
|

Classroom assessment in Greek primary schools

Abstract: This paper briefly presents some of the main findings concerning the implementation of assessment in Greek primary classrooms, from a study which explored the relation between teaching, learning and assessment in the primary classroom. It examines the assessment practices used; the purposes teachers attempted to fulfil when assessing; and the content of these assessments. The broader aim of the study was to present a general picture of assessment procedures in a typical Greek primary classroom. Classroom obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 99 publications
(266 reference statements)
1
4
0
2
Order By: Relevance
“…The rationale of this study is to investigate whether a new standardised Greek reading test can provide an alternative tool for the assessment of Greek primary education.Reading in Greece is taught as part of a linguistic lesson called 'My Language'. Assessment is an ongoing educational process, on the basis of which the pupil's learning progress is monitored (Kassotakis, 1994;Mavromatis, 1996). Its main aim in primary schools is to improve the students' learning by improving the teaching instruction and the operation of the schools.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale of this study is to investigate whether a new standardised Greek reading test can provide an alternative tool for the assessment of Greek primary education.Reading in Greece is taught as part of a linguistic lesson called 'My Language'. Assessment is an ongoing educational process, on the basis of which the pupil's learning progress is monitored (Kassotakis, 1994;Mavromatis, 1996). Its main aim in primary schools is to improve the students' learning by improving the teaching instruction and the operation of the schools.…”
mentioning
confidence: 99%
“…Students' assessments do not report only on the pupils' performance in the various subjects, but also on their other characteristics, such as their efforts, interests, initiative, creativity, cooperation with other people and respect for school regulations (Ypepth, 1994). According to Mavromatis (1996), classroom observations are the most widely used way for teachers to collect information about students' academic, behavioural and social characteristics.…”
mentioning
confidence: 99%
“…However, despite its important role, few researches have been identified on its purpose and function. One of the studies indirectly mentioned in feedback was conducted by Mavrommatis (1995), who found out that many teachers provided feedback to students in order to improve their performance. The majority of teachers stated that through the assessment process they control the degree of achievement of learning objectives, they plan, adopt and implement the necessary corrective measures to improve them and even motivate students to improve their learning status (Mavrommatis, 1995: 262).…”
Section: Through Feedback Teachers Evaluate and Abjust Their Teachinhmentioning
confidence: 99%
“…Περαιτέρω έρευνες, με εκπαιδευτικούς περισσότερων ειδικοτήτων, θα μπορούσαν ενδεχομένως να διαφωτίσουν περισσότερο το θέμα αυτό. (Elliot, 1997• Pintrich, 2004) και ότι οι αντιδράσεις των εκπαιδευτικών μπορούν να αποτελέσουν για τους μαθητές ένα βαρόμετρο ή ένα δείκτη για τις αξίες της σχολικής τάξης • Urdan, Kneisel, & Mason, 1999• Vermunt & Verloop, 1999 (Mavrommatis, 1996). Σε αντίθεση με τους εκπαιδευτικούς που συνηθίζουν να βάζουν υψηλούς βαθμούς για να «κερδίσουν» τους μαθητές, οι εκπαιδευτικοί της παρούσας έρευνας, που αναφέρουν υψηλή αντίληψη αυτοαποτελεσματικότητας για τη διαχείριση της σχολικής τάξης, δεν χρειάστηκε να καταφύγουν σε τέτοια μέσα.…”
Section: η επίδραση της ειδικότηταςunclassified